Circulation of human papillomavirus (HPV) genotypes in women from Córdoba, Argentina, with squamous intraepithelial lesions - Venezuela, Raul Fernando; Kiguen, Ana Ximena; Frutos, Maria Celia; Cuffini, Cecilia Gabriela (Revista do Instituto de Medicina Tropical de São Paulo, 2012)
Human papillomavirus (HPV) can induce a wide spectrum of squamous intraepithelial lesions (SIL) of varying severity. The aim of the present study was to establish the frequency of HPV infection and identify the genotypes circulating in women from Córdoba, Argentina, in relation to age and cytology. A total of 186 women, between 18 and 65 years old, with antecedents of SIL, underwent a pelvic examination and had cervical cells collected for cytology and HPV DNA detection. Ninety-six samples (51.6%) were positive for HPV detection, and sixty-three (65.6%) of them showed the presence of at least one HR-HPV. Low- and high-grade SIL showed significant association in patients younger than 35 years of age. We found 18 different genotypes, with a greater presence of HR-HPV. Genotypes 16 and 6 were the most frequent. Seven (7.3%) multiple infections, 85.7% of which had at least one HR-HPV, were detected. The detection of a large number of different HPV genotypes is a warning sign. It is thus necessary to strengthen the monitoring of the circulation of high-risk genotypes, currently less prevalent in intraepithelial lesions, as a control measure for the possible impact of the implementation of vaccines against genotypes 16 and 18.